If x = –2, y = 6 is solution of equation
3ax + 2by = 6, then
3a(-2) + 2b(6) = 6 -6a + 12b = 6
-a + 2b = 1 ...(1)
| dividing throughout by 6
Also
2(a - 1) + 2(3b - 4) = 4 2a - 2 + 6b -8 = 4
2a + 6b = 14
a + 3b = 7 ....(2)
| Dividing throughout by 2
Adding (1) and (2), we get
5b = 8 b =
Putting b = in (1), we get
Find two solutions for each of the following equations:
(i) 2x – 3y = 12 (ii) 2x – 5y = 0
(iii) 3y – 4 = 0.
Find the value of a so that the following equation may have x = 1, y = 1 as a solution:
3x + ay = 6
Write the equation in the form of ax + by + c =0. Check whether (0, 1) and
are the solutions of the equation.